Faktor-Faktor Yang Mempengaruhi Keberhasilan Usaha Penerima Bantuan KUBE Kanagarian Lakitan Tengah Kecamatan Lengayang Kabupaten Pesisir Selatan - Refina Saputri; Marwan Usman; Tri Kurniawati (Jurnal Ecogen, 2018)
The purpose of this research is to examine factors that affect  the Success of KUBE Business Kanagarian Lakitan Tengah Lengayang District, Pesisir Selatan Regency. The factors are entrepreneurship motivation, entrepreneurship ability and goverment supported. This research is descriptive quantitative, the population is the one who accept the assistance of KUBE business Kanagarian Lakitan Tengah Lengayang District, Pesisir Selatan Regency. This research uses the primer data. Method is regression analysis using SPSS 21. The  risults of this research has showed : 1) entrepreneurship motivation had significan positive influence to the KUBE Business Kanagarian Lakitan Tengah Lengayang District, Pesisir Selatan Regency  with the significan 0,012 < 0,05 2) entrepreneurship ability had significan positive influence to the KUBE Business Kanagarian Lakitan Tengah Lengayang District, Pesisir Selatan Regency with the significan 0,019 < 0,05. 3) goverment supported had significan positive influence to the KUBE Business Kanagarian Lakitan Tengah Lengayang District, Pesisir Selatan Regency with the significan 0,008< 0,05.4) entrepreneurship motivation, entrepreneurship ability, andgoverment supported had significan negative influence to the KUBE Business Kanagarian Lakitan Tengah Lengayang District, Pesisir Selatan Regency with the significan 0,010 < 0,05.Keywords: entrepreneurship motivation, entrepreneurship ability, goverment supported, and business success